Application of a color education software to improve color aptitude - Perge, Erika (Teaching Mathematics and Computer Science, 2015)
The ability to handle colors smoothly and consciously may be vital to professionals in various fields, including engineers specializing in architecture or design. Education in sciences related to colors and a developed color aptitude are essential. In our experience, many secondary school graduates in Hungary exhibit inadequate competence and need to be trained in both fields by college instructors, thereby laying the foundations for their future professional work. In our paper, we introduce a computer-based method to teach color theory using a self-developed interactive educational software. We also demonstrate the results of a test measuring the efficiency of the software. Our method was shown to be capable of familiarizing students with the basic fields of visual computing, e.g. graphics and image processing.